CHALLENGES OF ONLINE-EDUCATION: WHAT SOCIETY EXPECTS FROM TEACHERS - Zhukova, Oksana; Ivanenko, Lyudmila; Mandragelya, Vladimir; Janužis, Gintaras (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The main idea of the article is to present some characteristics of social expectations of teachers’ work that appeared after March 2020 when the whole world found itself in online education. These expectations are rather unified and do not depend on the level of economic development of the country or the degree of involvement in providing educational services online in the pre-Covid period. The article also attempts to analyse the challenges that teachers face while providing educational services online by dividing them in 3 groups: challenges related to students; challenges related to teachers, and challenges related to external factors. As the basis for the research, the results of an anonymous survey of teachers and lecturers from 6 countries were used. The results of the study show that social expectations and social requirements set for teachers and the education system in general by the society in the context of forced and total online education are excessive For writing the article, both theoretical (analysis, observation, reflection, etc.) and empirical (survey, static processing) research methods were used.